Non‐ambulatory dogs with cervical intervertebral disc herniation: single versus multiple ventral slot decompression. Issue 4 (23rd February 2020) - Guo, S; Lu, D; Pfeiffer, S; Pfeiffer, DU
Abstract : Objective: To evaluate the proportion of non‐ambulatory dogs with cervical intervertebral disc herniation (IVDH) in a private clinic and to compare signalment and outcome between those that underwent single or multiple ventral slot decompression (VSD). Design: Retrospective cohort study. Methods: After screening 43, 378 medical records (January 2010–September 2016), those of 185 dogs with non‐ambulatory tetraparesis or tetraplegia along with cervical IVDH that had undergone single (123) or multiple (62) VSD were included in this study. Data on signalment, preoperative neurological status, location of affected intervertebral disc(s), time to ambulation and short‐term outcome were compared between single and multiple VSD groups. Results: The proportion of non‐ambulatory dogs with IVDH was 35.3%. The prevalence of non‐ambulation was higher in male dogs (0.56%) than in female dogs (0.26%; P < 0.001) and in neutered dogs than in unneutered dogs (0.51% and 0.27%, respectively, P < 0.001). After surgery, 96.2% of the dogs reached ambulatory status. Dogs with multiple IVDH were older than those with single IVDH. Sex, neutering status or size did not affect the outcome or ambulation status postsurgery. The Pekingese was the most commonly affected breed in both groups. There was no difference in the time to reach ambulation and the presence of neurological deficits after surgery between dogs that underwent single and multiple VSD. Conclusions: In this cohort, dogs undergoing multiple VSD had a good postoperative outcome, and their short‐term functional recovery was equal to that of dogs undergoing single ventral slot compression.